Being angry, singing fast? Signalling of aggressive motivation by syllable rate in a songbird with slow song - Jaška, Pavel (Jihočeská univerzita, 2015)
In this study, we focused on the role of syllable rate in territorial interaction of chiffchaff males. We confronted each tested male with one of three playback types which differed in song rate (slow, non-manipulated, fast). The behaviour and the song of each subject were recorded before, during and after the treatment. Males that attacked the loudspeaker during playback sang faster before the stimulation. When birds continued singing during playback they increased syllable rate when exposed to fast or non-manipulated song. Our results indicate that syllable rate could be a signal of aggression in chiffchaff and play a role as a conventional signal rather than a handicap signal.
Being angry, singing fast? Signalling of aggressive motivation by syllable rate in a songbird with slow song
Keywords: bird song; syllable rate; vocal performance; male-male competition; Phylloscopus collybita; playback experiment; bird song; syllable rate; vocal performance; male-male competition; Phylloscopus collybita; playback experiment